Insulin resistance, diabetes mellitus and thyroid dysfunction in patients with palmoplantar pustulosis: a case-controlled study - Ataş, Hatice; Gönül, Müzeyyen (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Palmoplantar pustulosis (PPP) is a chronic pustular inflammatory skin disease; however, its pathogenesis is not well understood. Several factors, such as genetics, tobacco use and autoimmune issues, may contribute to this disease. Aim : This research was conducted to investigate the relationships between insulin resistance, thyroid disease and PPP. Material and methods : Thirty-three patients with PPP and 27 age- and gender-matched controls were analysed for their smoking histories, thyroid function tests, anti-thyroid peroxidase antibody (anti-TPO) levels, fasting glucose, fasting insulin levels and the homeostatic model assessment (HOMA) index for insulin resistance. Results : We found significant differences between the PPP and control groups according to their tobacco use and anti-TPO levels (p = 0.009 and p = 0.009, respectively). The proportion of tobacco use was 90% in the PPP patients and 63% in the controls. Gender and tobacco use were predictive risk factors for PPP in the multivariate analysis (OR = 141.7, p 35 U/ml and the presence of a thyroid abnormality were independent risk factors in the univariate, but not the multivariate analysis (OR = 4.2, p = 0.025 and OR = 5.4, p = 0.004, respectively). A moderate correlation between the gender and anti-TPO level was found (r = 0.361, p = 0.039); however, the fasting glucose, insulin and HOMA index were not significant between the PPP and control groups. Conclusions : Female gender and smoking were the most important risk factors for PPP; however, the increase in the anti-TPO level may be related to the predominance of females afflicted with this disease. Additional studies are necessary to clarify the relationships between PPP, thyroid disease and diabetes mellitus.